Pengaruh Work-Life Balance Dan Kompensasi Terhadap Kinerja Perawat (Studi Pada Rs. Antam Pomalaa) - Ismanto Ismanto; Fitri Kumalasari; Feby Febrianti Febrianti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2024)
This research aims to determine: (1) The effect of Work-Life Balance on nurse performance (Study at Antam Pomalaa Hospital). (2) The Effect of Compensation on Nurse Performance (Study at Antam Pomalaa Hospital). This research uses a quantitative method approach. Data collection in this research used observation, documentation and questionnaires. The population of this study were all nurses at Antam Pomalaa Hospital. Meanwhile, the sample for this study consisted of 34 nurses, the sample was determined using census techniques. Research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 3.0. Based on the research results, it is known that the Work-Life Balance variable has a positive and significant effect on Nurse Performance as indicated by a P-Values ​​value of 0.023. And the Compensation variable also has a positive and significant effect on Nurse Performance, this is indicated by a P-Values ​​value of 0.000.